The agrarian pact, sovereignty and food security in adaptation to climate change - Barrera Silva, Nubia (Universidad Francisco de Paula Santander, 2016)
The theme of this article corresponds to the most important historical event in more than half a century in the history of Colombia, not only for the signing of the Final Peace Agreement in Bogotá (2016), but also for the reconstruction of the agricultural sector of the small and medium owner. in the regions of Colombia. Although its execution is surrounded by great fissures, difficulties and an unexpected upsurge of violence against the life of the peasant, the Agrarian Pact is inscribed within the framework of the National Constitution, the Government and the State. In response to challenges and alternatives of the historic moment, the rural inhabitant victim of the armed conflict, has support and technical assistance from research centers of international organizations in cooperation with entities of the national agricultural sector, helping the Government to develop policies to respond to change climate. While there are unpredictable conflicts over land restitution, the cornerstone in the reconstruction of the countryside, social leaders also have a deep conviction and unwavering will to promote agricultural development in terms of sovereignty and food security.